Coastal sea level rise with warming above 2 °C - Jevrejeva, S; Jackson, L; Riva, R; Grinsted, A; Moore, J (National Academy of Sciences, 2016)
Two degrees of global warming above the pre-industrial level is widely suggested as an appropriate threshold beyond which climate change risks become unacceptably high. This ‘2° C' threshold is likely to be reached between 2040 and 2050 for both Representative Concentration Pathway (RCP) 8.5 and 4.5. Resulting sea level rises will not be globally uniform due to ocean dynamical processes and changes in gravity associated with water mass-redistribution. Here we provide probabilistic sea level rise projections for the global coastline with warming above the 2° C goal. By 2040, with a 2° C warming under the RCP8.5 scenario, more than 90% of coastal areas will experience sea level rise exceeding the global estimate of 0.2 m, with up to 0.4 m expected along the Atlantic coast of North America and Norway. With a 5° C rise by 2100, sea level will rise rapidly, reaching 0.9 m (median), and 80% of the coastline will exceed the global sea level rise at the 95th percentile upper limit of 1.8 m. Under RCP8.5 by 2100, New York may expect rises of 1.09 m, Guangzhou 0.91 m, and Lagos 0.90 m with the 95th percentile upper limit of 2.24 m, 1.93 m and 1.92 m respectively. The coastal communities of rapidly expanding cities in the developing world, and vulnerable tropical coastal ecosystems will have a very limited time after mid-century to adapt to sea level rises unprecedented since the dawn of the Bronze Age.